Good Practice Options for Sustainable Solid Waste Management in Mountain Areas of India, Nepal, and Pakistan - World Bank (World Bank, Washington, DC, 2021)
Solid waste management (SWM) is a vital responsibility of municipal governments worldwide and is one of the biggest challenges faced by urban authorities. Waste generation is increasing at a rapid pace, exceeding the financial and technical capacities of local governments to collect, treat, and dispose of this waste. In the South Asia region, India, Nepal, and Pakistan share one common geographic characteristic - the high peaks of the Himalayan mountain range. This unique mountain ecology presents an opportunity for these economies to leverage this natural asset for economic growth. The aim of this report is to showcase SWM practices: (1) currently underway in India, Nepal, and Pakistan that can be scaled-up and adopted across mountain communities, and (2) operational in other countries or in other sectors that can be applied to this region. In this way, mountain communities can learn of, and be inspired to adopt, innovations that can greatly improve service delivery and resource efficiency. Chapter one gives introduction. Chapter two provides an overview and synthesis of the good practice options presented in this report. The good practices are presented as individual chapters from chapters 3 to 22.